Acute Obstructive Hydrocephalus due to a Giant Posterior Cerebral Artery Aneurysm in a Pediatric Patient - DAĞÇINAR, ADNAN; BALTACIOĞLU, FEYYAZ; BAYRİ, YAŞAR; ŞAHİN, YENER (S. Karger AG, 2018)
Introduction: Intracranial aneurysms are very rare in children. Although subarachnoidal hemorrhage (SAH) is by far the most common presentation of aneurysms in the majority of the pediatric case series, it is not rare for an unruptured aneurysm to present with a mass effect. Acute hydrocephalus is a common finding following aneurysmal SAH. However, this malady may develop even in the absence of SAH but secondary to direct obstruction by a giant aneurysm. This situation is extremely rare in children, with only a few known case reports in the literature. Case Report: We report the case of a 10-year-old girl who presented with signs and symptoms of acute hydrocephalus; further radiological evaluation revealed obstructive hydrocephalus and a giant posterior cerebral artery aneurysm. Following endovascular treatment of the aneurysm, hydrocephalus was completely resolved, and the patient was symptom free. Conclusion: Although they are very rare, giant intracranial aneurysms must be kept in mind during the differential diagnosis of pediatric acute hydrocephalus cases. Hydrocephalus may resolve spontaneously after the successful treatment of these aneurysms. © 2018 S. Karger AG, Basel. Copyright: All rights reserved.
Keywords: Endovascular embolization; Obstructive hydrocephalus; Parent artery occlusion technique; Pediatric giant aneurysm; Shunting